Equity and the Sun Quality Health Private Provider Social Franchise: comparative analysis of patient survey data and a nationally representative TB prevalence survey - Montagu Dominic; Sudhinaraset May; Lwin Thandar; Onozaki Ikushi; Win Zaw; Aung Tin (BMC, 2013)
Abstract Introduction Since 2004, the Sun Quality Health (SQH) franchise network has provided TB care in Myanmar through a network of established private medical clinics. This study compares the wealth distribution of the TB patients to non-TB patients to determine if TB is most common among the poor, and compares the wealth of all TB patients to SQH TB patients to assess whether the franchise achieves its goal of serving the poor. Methods The study uses data from two sources: 1) Myanmar's first nationally representative TB prevalence study conducted in 2009, and 2) client exit interviews from TB patients from SQH clinics. In total, 1,114 TB-positive individuals were included in the study, including 739 from the national sample and 375 from the SQH sample. Results TB patients at SQH clinics were poorer than TB-positive individuals in the overall population, though not at a statistically significant level (p > 0.05). After stratification we found that in urban areas, TB patients at SQH clinics were more likely to be in the poorest quartile compared to general TB positive population (16.8% vs. 8.6%, respectively; p < 0.05). In rural areas, there was no statistically significant difference between the wealth distribution of SQH clinic patients and general TB positive individuals (p > 0.05). Conclusion Franchised clinics in Myanmar are reaching poor populations of TB patients in urban areas; more efforts are needed in order to reach the most vulnerable in rural areas.